Saharan dust over a central European EARLINET-AERONET site : Combined observations with Raman lidar and Sun photometer - Mueller, D.; Mattis, I.; Wandinger, U.; Ansmann, A.; Althausen, D.; Dubovik, O.; Eckhardt, S.; Stohl, A. (Journal of Geophysical Research, 2003)
[1] Combined observations with an advanced aerosol water-vapor temperature Raman lidar and a Sun photometer are used for a detailed characterization of geometrical and optical properties of a continental-scale Saharan dust event observed over Leipzig ( 51.3 degreesN, 12.4 degreesE), Germany, from 13 to 15 October 2001. The Raman lidar is part of the European Aerosol Research Lidar Network (EARLINET). Automatic observations of aerosol optical depth and sky brightness are made with the Sun photometer in the framework of the worldwide operating Aerosol Robotic Network (AERONET). The dust plume reached a top height of 6000 m. Sun photometer and lidar observations showed a constant increase of columnar optical depth at 532 nm from 0.25 on 13 October 2001 to a maximum of similar to0.63 on 14 October 2001. According to observations with lidar, up to 90% of the optical depth at the wavelength of 532 nm was contributed by the dust layer above 1000-m height. Angstrom exponents from Sun photometer observations between 380 and 1020 nm were similar to0.45 at the beginning of the dust period, and dropped to minimum values of 0.14 during the peak of the dust outbreak. Vertically resolved Angstrom exponents derived from lidar profiles of the extinction coefficients at 355 and 532 nm showed a strong variability with values as low as -0.2 in the center of the dust plume. Below 1000-m height column-averaged Angstrom exponents strongly varied between 1.0 in the beginning of the dust period and 0.39 on 14 October 2001 when the dust penetrated into the boundary layer. Comparison of column-averaged optical depth and Angstrom exponents derived from lidar and Sun photometer observations showed excellent agreement. Particle depolarization ratios of up to 25% were derived from lidar observations at 532 nm. Scattering phase functions retrieved from Sun photometer observations indicated particles of nonspherical shape. This shape caused unusually large particle extinction-to-backscatter ( lidar) ratios at 532 nm in the range from 50 to 80 ...